Population study of Allium altaicum Pall. in Kazakhstan Altai - Danilova, A.N.; Sumbembayev, A.A. (Fundamental and Experimental Biology, 2023)
The purpose of this work was population studies of Allium altaicum Pall. on the territory of the Kazakhstan Altai in 3 territorially isolated geographical regions: Southern, South-Western Kalba Altai. As a result of the survey of the territory by the route-reconnaissance method on the ridges of Sarymsacty, Lineysky and Kalba, a study was made of populations that are characterized by different environmental conditions and altitudinal limits. Ecological and phytocenotic screening revealed that on the Sarymsactyridge the population is located in the alpine belt in the altitudinal limit of 1870 m a.s.l., on the Lineyskyridge ‒ in the mountain-forest, 1361 m.a.s.l.Both populations are characterized by meso-psychro-petrophytic growing conditions. On the ridge ridgeKalba, the population was examined in the mountain-steppe xero-meso-petrophytic conditions, 832 m a.s.l. Soils are mountain chernozems, slightly acidic, pH 5.6–5.9, with a high humus content from 13.5% to 14.9%, the ground cover is formed, 210–410 g/m2.In all populations, the vegetation cover is based on herbaceous perennials; layering is not pronounced. Participation of A. altaicum in the formation of phytocenosis on the ridge Sarymsacty is 3.2%, Lineysky ‒ 2.2%; Kalba ‒ 1.8%. The florocomplex of the surveyed populations is formed from 91 species of vascular plants.The similarity of the floristic compositions of the Sarymsacty population in alpine meso-psychro-petrophytic conditions and Lineysky in mountain-forest meso-psychro-petrophytic conditions at the level of 65.0% in relation to the entire cenoflora was established, and Kalba in mountain-steppe xero-meso-petrophytic conditions this figure was 42.1%. Variability of morphometric parameters of aboveground organs of A. altaicum in all examined populations has an average and high level of variability from 15.0 to 26.09%, which indicates the ecological plasticity of plants. It has been established that in nature vegetative reproduction occurs only in virginal and generative plants, and nests are formed. The biomorphological parameters of the bulbs in the nest have a clearly expressed age character and vary within the same coenopopulation.